The Gap Between Social Functioning to Emotional Functioning Among Young Adolescents with Nocturnal Enuresis - Sagie, Tal (Wydawnictwo Naukowe UAM, 2014)
For many decades, Nocturnal Enuresis (NE, Bedwetting) has been investigated mainly among children. There are many studies that have checked the impact of NE on the social and emotional functioning of children, but less focus was given on young adolescence and adolescence. The first part of this article will shed more light on NE in general. The second part will discuss the social and emotional functioning of enuretics. The third part will focus on young adolescents with NE. The last part of this article will suggest a new gap model, between the social to the emotional state of the enuretic young adolescent. This gap will be explained in perspective of the Self-Discrepancy theory (SDT).
Różnice pomiędzy zachowaniami społecznymi a emocjonalnymi u dzieci z moczeniem nocnym
Keywords: pedagogy; psychology; therapy; nocturnal enuresis; emotional functioning, social functioning; adolescents; developmental delay; self-discrepancy theory